Ocena częstości współwystępowania bólu głowy i kręgosłupa oraz objawom im towarzyszącym = Assessment of the frequency of the co-occurrence of headaches and back pain and associated with them symptoms - Kozłowski, Piotr; Kozłowska, Magdalena (Journal of Education, Health and Sport, 2016)
Kozłowski Piotr, Kozłowska Magdalena. Ocena częstości współwystępowania bólu głowy i kręgosłupa oraz objawom im towarzyszącym = Assessment of the frequency of the co-occurrence of headaches and back pain and associated with them symptoms. Journal of Education, Health and Sport. 2016;6(8):210-218. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.60216 http://ojs.ukw.edu.pl/index.php/johs/article/view/3749 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.07.2016. Revised 25.07.2016. Accepted: 12.08.2016. Ocena częstości współwystępowania bólu głowy i kręgosłupa oraz objawom im towarzyszącym Assessment of the frequency of the co-occurrence of headaches and back pain and associated with them symptoms Piotr Kozłowski1, Magdalena Kozłowska2 1Katedra Anatomii Człowieka, Zakład Anatomii Prawidłowej, UM w Lublinie 2Katedra i Klinika Neurologii, UM w Lublinie Uniwersytet Medyczny w Lublinie ul. W. Chodźki 1, 20-093 Lublin e-mail: piotr7176@gmail.com Streszczenie Celem pracy była ocena częstości współwystępowania bólu głowy i kręgosłupa. W badaniu oceniono styl życia pacjentów z dolegliwościami bólowymi głowy i kręgosłupa. Ankietowani odpowiedzieli na pytania dotyczące poziomu natężenia bólu, czasu trwania dolegliwości bólowych oraz objawom im towarzyszącym. Badaniem objęto 103 osób. Kobiety stanowiły 56,9% respondentów, natomiast mężczyźni 43,1%. Wiek ankietowanych zawierał się pomiędzy 18 a 75 lat. Badanie przeprowadzono w okresie od stycznia do marca 2016 roku metodą wywiadu standaryzowanego. Narzędziem użytym do zebrania danych był autorski, anonimowy kwestionariusz. Kwestionariusz zawierał 43 pytania z możliwością jednokrotnego wyboru w tym trzy pytania z możliwością wielokrotnego wyboru. Przeprowadzono analizę statystyczną z wykorzystaniem testu chi- kwadrat. Wszystkie wartości w których p<0,05 uznano za istotne statystycznie. Wszyscy ankietowani skarżyli się na dolegliwości bólowe głowy, niewiele mniej ankietowanych skarżyła się na ból kręgosłupa (93,2%). Na pytanie przez jaki okres czasu występują dolegliwości bólowe głowy 36,4% respondentów wskazała, że około 1 godzinę, ponad 30% ankietowanych zgłasza ból głowy trwający ponad 3 godziny, u jednej piątej ankietowanych ból utrzymuje się 2-3 godziny. Respondenci istotnie statystycznie (p<0,05) częściej potrafili określić lokalizację bólu. Ankietowani z podobną częstością wskazywali ból w okolicy skroniowej (27,7%) oraz w okolicy potylicznej (24,8%). Najczęstszym objawem towarzyszącym dolegliwościom bólowym głowy była zmiana nastroju (66,3%, p<0,05). Ankietowani najczęściej odczuwają ból pleców zlokalizowany w odcinku lędźwiowym (75%, p<0,05). Kobiety istotnie statystycznie częściej (p<0,05) wskazywały na ból umiejscowiony w odcinku szyjnym (83,7% ankietowanych w tej grupie). Na pytanie o to czy w czasie doby zmienia się nasilenie bólu 81,3% ankietowanych wskazała, że charakter bólu ulega zmianie w ciągu doby, jest to wartość istotna statystycznie (p<0,05). Słowa kluczowe: ból głowy, ból kręgosłupa, styl życia, migrena. Abstract The aim of this study was to evaluate the prevalence of headaches and back pain in relation to the quality of life of people suffering from this kind of pain. Respondents answered questions about the level of pain intensity, duration of pain and symptoms accompanying them. The study involved 103 people. Women accounted for 56.9% of the respondents, men- 43.1%. The age of the respondents was between 18 and 75 years of age. The study was conducted from January to March 2016 and implemented the standardized interview method. The tool used for data collection was an anonymous questionnaire. The questionnaire contained 43 single-choice questions and three multiple-choice questions. Statistical analysis was performed using chi-square test. All values for which p<0.05 were considered statistically significant. All respondents complained of headaches and almost all respondents complained of back pain (93.2%). To the question regarding the duration of headache, respondents most often (36.4%) indicated that it usually lasted about 1 hour, more than 30% of respondents reported headache lasting more than three hours, one-fifth of the responders pain lasted about 2-3 hours. Statistically significant respondents (p <0.05) were more likely to precisely identify the location of headache. Respondents with similar frequency indicated pain in the temporal (27.7%) and occipital (24.8%) region. The most common symptoms associated with headaches were mood swings (66.3%, p <0.05). The respondents most often felt pain in the lumbar section (75%, p <0.05). Women significantly more often (p <0.05) indicated pain located in the cervical section (83.7% of respondents in this group). To the question of whether during the day the severity of pain changed, 81.3% of the respondents gave an answer that the nature of pain changed throughout the day (a statistically significant value, p <0.05). Key words: headache, back pain, life style, migraine.